Humiliation. Social Anatomy of a Dark Emotion - Araya, Fernando (Simmel Studies, 2020)
Humiliation is both an emotional state and the social situation that produces it as well. This paper inquires into both dimensions, departing from Georg Simmel’s perspective and questions in his sociology of emotions, especially his thoughts on shame. Based on historical cases and literary examples, the paper analyzes humiliation as a composite emotional state (mixture of shame, wrath and sadness), and the distinctive features of it as a «form» of interaction. Regarding the latter, it is highlighted (a) its relational character, (b) the realization of a type of action whose purpose is degrading, (c) a representation of human value which is injured precisely by that action, and usually (d) its public character. It is warned about the main effects that humiliation may have at the subjective (resentment and thirst for revenge) and at the social level (increase of conflict, maintenance or instauration of an asymmetrical balance of forces, divisive effect and social stigmatization). In view of such negative consequences, the essay concludes by considering the main ways in which humiliation could be limited in our social life.